Molecular cloning, DNA sequencing, and enzymatic analyses of two Escherichia coli pyruvate oxidase mutants defective in activation by lipids. - Chang, Y Y (1986)
Two Escherichia coli pyruvate oxidase (EC 1.2.2.2) mutant genes, poxB3 and poxB4, were cloned on plasmid pBR322. The poxB3 mutant oxidase which was described previously (Y. Y. Chang and J. E. Cronan, Jr., Proc. Natl. Acad. Sci. USA 81:4348-4352, 1984) was deficient in lipid activation but retained full catalytic activity. The poxB3 mutation was located in the C-terminal half of the gene, and the nucleotide alteration has been determined by DNA sequencing of this part of the gene and by comparing the sequence with that of the wild-type strain (C. Grabau and J. E. Cronan, Jr., submitted for publication). The poxB3 oxidase mutation is the substitution of a serine residue for Pro-536. poxB4, another pyruvate oxidase mutant gene, was also deficient in lipid activation. The major difference between the poxB3 and poxB4 oxidase was in the binding of Triton detergents. The poxB4 mutation was also located in the C-terminal half of the gene, and sequence analysis has shown that only one nucleotide base was altered, which resulted in Ala-467 being converted to a threonine residue. The results of the amino acid substitutions in the mutant proteins, leading to the functional alteration of the enzyme, are discussed.